The Effects of Bank Specific Factors on Banks Profitability: Panel Data Analysis on Turkish Banking System - Yaman, Serdar (Şırnak Üniversitesi, 2021)
In this study, bank specific factors affecting the profitability of banks are analyzed by panel data analysis. The study covers annual data for the period 2009-2018 of 20 commercial banks operating in Turkey. In the study, the effects of bank specific factors on banks’ return on assets, return on equity and net interest margins are analyzed by separate models and compared. As a result of the study, it has been determined that the factors of capital adequacy, deposits, investments on financial assets and credits, ability to pay short term debts and ability to convert expenses into revenues have positive effects on banks profitability and that the factors of loans, liquid assets and personnel expenses have negative effects. In the study it has also been determined that the capital adequacy, credit investments, ability to convert expenses into revenues, market shares and personnel expenses have positive effects on net interest margins and that deposits have negative effects.

Bu çalışmada, mevduat bankalarının karlılıklarına etki eden içsel faktörlerin panel veri analizi yöntemi ile incelenmesi amaçlanmıştır. Çalışma, Türkiye’de faaliyet gösteren 20 mevduat bankasının 2009-2018 dönemine ait yıllık verilerini kapsamaktadır. Çalışmada, bankalara özgü faktörlerin banka aktif karlılıkları, özsermaye karlılıkları ve net faiz marjlarına olan etkiler ayrı modeller ile incelenmiş ve karşılaştırılmıştır. Çalışma sonucunda, sermaye yeterliliği, mevduatlar, finansal varlık ve kredi yatırımları, kısa vadeli borçları ödeyebilme ve giderleri gelirlere dönüştürebilme kabiliyeti faktörlerinin karlılık üzerinde pozitif etkiye sahip olduğu; alınan krediler, likit aktifler ve personel giderleri faktörlerinin ise negatif etkiye sahip olduğu tespit edilmiştir. Çalışmada ayrıca, sermaye yeterlilikleri, kredi yatırımları, giderleri gelirlere dönüştürülebilme kabiliyeti, pazar payları ve personel giderlerinin net faiz marjı üzerinde pozitif etkiye sahip olduğu; mevduatların ise negatif etkiye sahip olduğu tespit edilmiştir.
BANKALARA ÖZGÜ FAKTÖRLERİN BANKA KARLILIĞINA ETKİSİ: TÜRKİYE BANKACILIK SEKTÖRÜ ÜZERİNE PANEL VERİ ANALİZİ